Moth assemblages in Costa Rica rain forest mirror small‐scale topographic heterogeneity. (30th June 2019) - Rabl, Dominik; Gottsberger, Brigitte; Brehm, Gunnar; Hofhansl, Florian; Fiedler, Konrad
Abstract: In many tropical lowland rain forests, topographic variation increases environmental heterogeneity, thus contributing to the extraordinary biodiversity of tropical lowland forests. While a growing number of studies have addressed effects of topographic differences on tropical insect communities at regional scales (e.g., along extensive elevational gradients), surprisingly little is known about topographic effects at smaller spatial scales. The present study investigates moth assemblages in a topographically heterogeneous lowland rain forest landscape, at distances of less than a few hundred meters, in the Golfo Dulce region (SW Costa Rica). Three moth lineages—Erebidae–Arctiinae (tiger and lichen moths), the bombycoid complex, and Geometridae (inchworm moths)—were examined by means of automatic light traps in three different forest types: creek forest, slope forest, and ridge forest. Altogether, 6, 543 individuals of 419 species were observed. Moth assemblages differed significantly between the three forest types regarding species richness, total abundance, and species composition. Moth richness and abundance increased more than fourfold and eightfold from creek over slope to ridge forest sites. All three taxonomic units showed identical biodiversity patterns, notwithstanding their strong differences in multiple eco‐morphological traits. An indicator species analysis revealed that most species identified as characteristic were associated either with the ridge forest alone or with ridge plus slope forests, but very few with the creek forest. Despite their mobility, local moth assemblages are highly differentially filtered from the same regional species pool. Hence, variation in environmental factors significantly affects assemblages of tropical moth species at small spatial scales. Abstract in Spanish is available with online material. Resumen: En el bosque lluvioso tropical de tierras bajas, la variación topográfica incrementa la heterogeneidad ambiental y, por lo tanto, contribuye a una elevada biodiversidad. Mientras un número creciente de estudios han hablado del efecto de las diferencias topográficas en las comunidades de insectos tropicales a escalas regionales (p.e. a lo largo de extensos gradientes altitudinales), sorprendentemente poco es conocido sobre el posible efecto topográfico en dichos grupos a escalas locales. El presente estudio trata sobre dicho efecto a distancias menores a unos pocos cientos de metros, en comunidades de polillas en bosque lluvioso de tierras bajas topográficamente heterogéneas en la región de Golfo Dulce (SW Costa Rica). Tres linajes de polillas ‐Erebidae‐Arctiinae (polillas tigre y liquen), bombycoid‐complex y Geometridae (geométridos)—fueron colectadas con trampas de luz automáticas en tres tipos diferentes de bosque: bosque de valle, bosque de ladera y bosque tope. En total, 6543 individuos de 419 especies fueron observados. Las comunidades de polillas difirieron significativamente entre los tres tipos de bosques en cuanto a la riqueza de especies, abundancia total y grupos de especies. La riqueza y la abundancia incrementaron más de cuatro veces desde bosque de valle sobre bosque de ladera hasta bosque tope. Las tres unidades taxonómicas mostraron patrones idénticos de biodiversidad, a pesar de grandes diferencias en las múltiples características eco‐morfológicas. Un análisis de especies indicadoras reveló que la mayoría de especies identificadas como diagnósticas fueron asociadas tanto con bosque tope solo, o con bosque tope y bosque de ladera, pero no con bosque de valle. A pesar de su movilidad, los conjuntos de polillas locales son filtrados de manera muy diferente del mismo grupo regional de especies. Por lo tanto, la variación en los factores ambientales, dejan un distintivo característico en estos grupos a esta pequeña escala espacial.